Expansion of the mutation spectrum and phenotype of USP7-related neurodevelopmental disorder - Zheng, Hong; Mei, Shiyue; Li, Fuwei; Wei, Liwan; Wang, Yanchu; Huang, Jinrong; Zhang, Feng; Huang, Jia; Liu, Yanping; Gu, Weiyue; Liu, Hongyan (Frontiers in Molecular Neuroscience, 2022)
Abstract Background: Hao-fountain syndrome (HAFOUS) is a neurodevelopmental syndrome with global developmental delay, severe language delay, behavioral abnormalities (including autism), and mild dysmorphic impairment of intellectual development. The disease is a dominant genetic disease caused by mutations in the USP7 gene (*602519) on chromosome 16p13.2. To date, only 15 cases with 14 deleterious variants in the USP7 gene have been reported. Methods: Here, we describe three unrelated individuals with USP7 variants. Three novel de novo heterozygous USP7 variants were identified using trio-whole exome sequencing and verified by Sanger sequencing. Clinical features were evaluated by reviewing medical records. Results: The three variants identified in this study, including one frameshift variant (c.247_250delGAGT) and two missense variants (c.992A>G, c.835T>G) have not been previously reported. The predominant clinical manifestations of these three individuals were DD/ID, language impairment, abnormal behavior, and abnormal brain magnetic resonance(dilation of lateral ventricles, dilation of Virchow-Robin spaces,dilated third ventricle，abnormal cerebral white matter morphology in bilateral occipital lobes, hypodysplasia of the corpus callosum, arachnoid cyst, delayed myelination, widened subarachnoid space); some also had facial abnormalities. Conclusions: DD/ID is the most common clinical phenotype of HAFOUS, although some patients also exhibit language and behavioral abnormalities. We identified three variants of USP7 for the first time in China using whole-genome sequence data. This study not only expanded the USP7 mutation spectrum but also provided more clinical data regarding the clinical phenotype of HAFOUS. Keywords: USP7 gene; Neurodevelopmental disorder; Hao-fountain syndrome; Whole exome sequencing; molecular spectrum